2015
DOI: 10.1155/2015/708908
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Impact of Workplace Bullying: Humanistic and Economic Burden among Workers with Chronic Medical Conditions

Abstract: Background. Although the prevalence of work-limiting diseases is increasing, the interplay between occupational exposures and chronic medical conditions remains largely uncharacterized. Research has shown the detrimental effects of workplace bullying but very little is known about the humanistic and productivity cost in victims with chronic illnesses. We sought to assess work productivity losses and health disutility associated with bullying among subjects with chronic medical conditions. Methods. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…A recent study has calculated the burden on workers’ quality of life and productivity associated with workplace bullying and found that the adjusted marginal overall productivity cost ranged from ~15%, corresponding to Italian Purchase Power Parity 2010, which amounted to US$4,182–5,236 yearly. 65 Thus, the question is, how is a given department affected when a bully perpetrates negative behaviors but the direct supervisor does nothing, legitimating then the bullying process? And how is the whole organization impacted?…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has calculated the burden on workers’ quality of life and productivity associated with workplace bullying and found that the adjusted marginal overall productivity cost ranged from ~15%, corresponding to Italian Purchase Power Parity 2010, which amounted to US$4,182–5,236 yearly. 65 Thus, the question is, how is a given department affected when a bully perpetrates negative behaviors but the direct supervisor does nothing, legitimating then the bullying process? And how is the whole organization impacted?…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in work productivity have established that greater disease severity is associated with worse work productivity and worse quality of life. Fattori et al, 2015 (Italy) SF-12 WPAIQ n = 1,717 Patients with autoimmune arthritis, major depression disorder, psoriasis, inflammatory bowel disease 81% of subjects who experienced workplace bullying had a preexisting medical condition before the bullying started. Patients who experienced bullying had much higher WPAI scores and worse QoL scores compared with those who were not bullied.…”
Section: Quality Of Lifementioning
confidence: 99%
“… Fattori et al (2015) established a link between workplace bullying and work productivity in a study that used the WPAIQ in patients with one of four chronic conditions, including major depressive disorder, psoriasis, autoimmune arthritis, and inflammatory bowel disease. A total of 81% of patients who experienced workplace bullying had a preexisting medical condition before the bullying started.…”
Section: Work Productivity In Other Dermatological Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Victims of workplace bullying also reported sleep disturbances2 and suicidal ideation 3 4. The productivity loss (absenteeism and presenteeism combined) due to workplace bullying was between 13.9% and 17.4% of working hours 5…”
Section: Introductionmentioning
confidence: 99%